Forces during landing on competition mats in gymnastics vaulting - Payne, E. L. (University Loughborough, 2015)
The new vaulting table was introduced in 2001. This has resulted in an increase in difficulty of the skills being performed by male and female gymnasts. As a consequence of the increasing skill difficulty, the heights from which gymnasts land has also increased. Gymnasts have been reported to reach peak vertical heights of up to 3 meters above the landing surface (Takei, 2007). The F.I.G. apparatus norms (2011) state that the rules for vault landings are the use of a 200 mm thick landing mat with a compulsory supplementary 100 mm mat placed on top. During these landings gymnasts need to withstand high impact forces and previous research has highlighted the possible connection between external landing forces and injury (Nigg, 1983). It was the aim of this research to investigate landing mat properties and gymnastics vault landing forces. This was achieved through experimental and theoretical research. Equipment testing procedures were established for impactor drops and gymnast landings with the use of F.I.G. standard landing mats (onto one and two landing mat conditions) with a force platform and a Vicon motion capture system. Landing mat and gymnast properties were established to be used as an input for spring-mass model. Parameters such as the maximum landing forces, mat effective mass and landing mat stiffness were established. Experimental results concluded that gymnasts are able to adjust their landing strategy to restrict the maximum forces experienced when landing on different surfaces. An observed reduction in initial force and the forces at the foot-mat surface may make landing onto two landing mats the preferred set-up for a gymnast who is performing numerous landings in practice and competitions. Mat stiffness for both one and two landing mats was concluded to have a non-linear relationship for the force-depression curves. Additionally, a spring-mass model of the gymnast landings demonstrated that a reduction in the mat stiffness and damping resulted in a decrease in the maximum force. With an increase in time to this maximum force the loading rates during gymnast landings were also reduced.